Improvement of health-related quality of life and adherence to treatment with calcipotriol-betamethasone dipropionate gel in patients with psoriasis vulgaris - George Kontochristopoulos; Anargyros Kouris; Athanasios Chantzaras; Athanasios Petridis; John Yfantopoulos (Sociedade Brasileira de Dermatologia, 2016)
Abstract BACKGROUND: Psoriasis is a common, chronic, recurrent, immune-mediated disorder of the skin and joints. It can have a significant negative impact on the physical, emotional and psychosocial wellbeing of affected patients. OBJECTIVES: To measure improvement in health-related QoL (HRQoL) in Greek patients with psoriasis vulgaris after a month of treatment with calcipotriol-betamethasone dipropionate gel; and evaluate adherence to treatment parameters. METHODS: The study included 394 psoriasis vulgaris patients from 16 private dermatological practices in Greece, all treated with calcipotriol-betamethasone dipropionate gel. They were evaluated at the first visit and after 4 weeks. Moreover, they completed the Dermatology Life Quality Index (DLQI), while other data such as disease severity, subjective symptoms and adherence, were collected. RESULTS: At week 4, the DLQI median was reduced by 3.5 points from the baseline (p<0.001; baseline and week 4 median: 4.5 and 1.0 respectively). Pruritus and sleep disorders also improved (p<0.001). Furthermore, 90.1% of the subjects fully adhered to treatment, with a 97.1% mean level of compliance. CONCLUSIONS: The convincing clinical results, with a distinct improvement in HRQoL, plus the high level of adherence due to its advantageous physical properties, make the calcipotriol-betamethasone dipropionate gel formulation an important, effective and well-tolerated topical therapy to treat psoriasis.